Design and simulation of electronic circuit - Ng, Kelvin Hon Seng (Nanyang Technological University, 2022)
With the advancement of technology, microcontroller (MCUs) has been an integral part of today’s society. With the rise of popularity for its functionality and processing capability, MCUs are used on almost all electronic systems. 8 and 16-bit processors are typically used for low processing capacity due to the ease of implementation and low cost. While 32 and 64-bit processors are used for high processing capacity. The selection of microcontrollers is different based on the choice of integrated circuits, operating environments, and programming complexity